The hatred of literature - Marx, William 1966- (The Belknap Press of Harvard University Press, 2018)
For 2,500 years literature has been condemned in the name of authority, truth, morality and society. But in making explicit what a society expects from literature, anti-literary discourse paradoxically asserts the validity of what it wishes to deny. The threat to literature's continued existence, William Marx writes, is not hatred but indifference....
"This book was originally published in French as La haine de la litterature (c) 2015 by Les Editions de Minuit, 7, rue Bernard-Palissy, 74006 Paris.". - Includes bibliographical references and index
Keywords: Geschichte; Censorship -- History; Prohibited books -- History; Literature and morals -- History; Literature -- History and criticism; Verfolgung; Literatur; Zensur